Pengaruh Pendidikan Karakter Terhadap Disiplin Anak Usia Dini Usia 5-6 Tahun di TK GKPI Tarutung Kota - Deby Rani Simanjuntak (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study was to determine the effect of character education on the discipline of early childhood aged 5–6 years at TK GKPI Tarutung Kota. This study employed a quantitative research method. The population consisted of all early childhood students aged 5–6 years who were registered and actively participating in learning activities at TK GKPI Tarutung Kota, totaling 113 students. The research sample was 26 students, representing 25% of the total population, selected using a random sampling technique. Data were collected using a closed-ended questionnaire consisting of 20 items, with 10 items measuring variable X and 10 items measuring variable Y.The results of data analysis indicated that there is a significant influence of character education on early childhood discipline aged 5–6 years at TK GKPI Tarutung Kota, as evidenced by the following findings: (1) Analysis prerequisite tests: (a) the normality test showed an Asymp. Sig. (2-tailed) value of 0.200 > 0.05; (b) the linearity test showed a significance value of deviation from linearity of 0.461 > 0.05. (2) Correlation tests: (a) the positive relationship test yielded rxy = 0.546 > rtable (α = 0.05, n = 26) = 0.388, indicating a positive relationship between variables X and Y; (b) the significance test yielded tcount = 3.192 > ttable (α = 0.05, df = n–2 = 24) = 2.064, indicating a significant relationship between variables X and Y. (3) Influence tests: (a) the regression equation test resulted in Ŷ = 16.743 + 0.477X; (b) the coefficient of determination (r²) was 29.8%. (4) Hypothesis testing using the F-test showed that Fcount > Ftable (α = 0.05; numerator df = 1; denominator df = 25), namely 10.189 > 4.24. Thus, the alternative hypothesis (Ha), which states that “there is a significant influence of character education on early childhood discipline aged 5–6 years at TK GKPI Tarutung Kota,” is accepted, while the null hypothesis (H0) is rejected.